Sex disparity in the association between alcohol consumption and sarcopenia: a population-based study - Yang, Longbao; Ran, Qiuju; Yeo, Yee Hui; Wen, Zhang; Tuo, Shuyue; Li, Yong; Yuan, Jia; Dai, Shejiao; Wang, Jinhai; Ji, Fanpu; Tantai, Xinxing (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have shown inconsistent findings regarding the association of alcohol consumption with sarcopenia. Therefore, this study comprehensively investigated the association of alcohol consumption with sarcopenia in a nationally representative sample of US adults.MethodsThis population-based study included adults aged 18 years and older from the National Health and Nutrition Examination Survey (NHANES) III. Alcohol exposure was defined as daily alcohol intake, alcohol drinking history, number of drinking days per week, and frequency of binge drinking days per month. Weighted logistic regressions were used to determine associations.ResultsFour cohorts were selected from the NHANES III: cohort 1 (n = 7,592), cohort 2 (n = 12,060), cohort 3 (n = 7,608), and cohort 4 (n = 7,649), corresponding to alcohol exposure categories of daily alcohol intake, drinking history, number of drinking days per week, and frequency of binge drinking days per month. In the full model, the risk of sarcopenia was significantly associated with mild (odds ratio [OR]: 1.65; 95% confidence interval [CI]: 1.08–2.51), moderate (OR: 2.04; 95% CI: 1.12–3.71), and heavy drinkers (OR: 2.42; 95% CI: 1.17–4.97) compared to nondrinkers. There was an association between the development of sarcopenia and current drinkers (OR: 1.69; 95% CI: 1.12–2.56) but not former drinkers (OR: 1.21; 95% CI: 0.88–1.66). Compared to nondrinkers, an increased risk of developing sarcopenia was observed in participants who consumed alcohol 2 days (OR: 2.36; 95% CI: 1.40–3.99) or > 2 days (OR: 1.84; 95% CI: 1.10–3.07) per week, and those who engaged in binge drinking for ≤1 day per month (OR: 1.68; 95% CI: 1.09–2.60) or > 1 day per month (OR: 2.10; 95% CI: 1.10–4.01). Sensitivity analyses based on different definitions of sarcopenia yielded similar results. Stratified analyses revealed that these associations were present in females but not males.ConclusionAlcohol intake was associated with an increased risk of sarcopenia in all individuals, with this association being primarily observed in females rather than males.